Leptospirosis acquisition following the reintroduction of wildlife. (31st October 2015) - Gelling, M.; Zochowski, W.; Macdonald, D. W.; Johnson, A.; Palmer, M.; Mathews, F.
Abstract : Potential risks posed to domestic animals and human beings by zoonotic diseases in reintroduced animals can reduce the acceptability of reintroductions. The authors investigated the role of endangered water voles, Arvicola amphibius, as a host for leptospirosis, a waterborne zoonosis affecting a range of mammals. Based on samples from 112 individuals from across the UK, a 6.2 per cent exposure rate was found (7 animals were microscopic agglutination test (MAT) positive for serum antibodies), with 4 of 11 sites having positive animals. No individual was actively excreting leptospires in urine (PCR urine test, 0 per cent positive). The acquisition of Leptospira species by a cohort of 'clean' captive‐bred voles reintroduced to one site in the wild was then examined. By four months postrelease the maximum exposure prevalence (by either MAT or culture) was 42.9 per cent. Thirty‐five per cent were actively excreting leptospires. The rapidity of leptospire acquisition and comparatively high prevalence of infectious individuals is notable, exceeding expectation based on wild voles. One possible explanation is a lack of immunocompetence in reintroduced voles. Analyses of haematological parameters from reintroduced voles suggest a link between prior condition and disease acquisition. There may be potential to select the fittest animals before release to maximise reintroduction success.